A Bibliometric Study on the Evolution of Corporate Governance Research - Judijanto, Loso (West Science Accounting and Finance, 2025)
This study presents a comprehensive bibliometric analysis of corporate governance research published between 2000 and 2025, aiming to map its intellectual structure, thematic evolution, and global collaboration patterns. Utilizing data from the Scopus database and visualized through VOSviewer, the study analyzes co-authorship networks, co-citation clusters, keyword co-occurrence, and country collaborations. The findings reveal that traditional governance themes, such as board composition, ownership structure, and financial performance remain central, anchored by foundational theories like agency theory. However, there is a notable thematic shift toward emerging topics including sustainability, stakeholder engagement, social responsibility, and risk management, reflecting the growing influence of ESG considerations. Co-citation analysis identifies key intellectual contributors, while country collaboration mapping shows strong leadership from the United States and increasing engagement from emerging economies. This study provides valuable insights into the progression and diversification of corporate governance research, highlighting opportunities for more context-specific, inclusive, and future-oriented scholarly exploration.